Desiderata for Controlled Medical Vocabularies in the Twenty-First Century - Cimino, J. J. (Methods of Information in Medicine, 1998)
Builders of medical informatics applications need controlled medical vocabularies to support their applications and it is to their advantage to use available standards. In order to do so, however, these standards need to address the requirements of their intended users. Overthe past decade, medical informatics researchers have begun to articulate some of these requirements. This paper brings together some of the common themes which have been described, including: vocabulary content, concept orientation, concept permanence, nonsemantic concept identifiers, polyhierarchy, formal definitions, rejection of “not elsewhere classified” terms, multiple granularities, mUltiple consistent views, context representation, graceful evolution, and recognized redundancy. Standards developers are beginning to recognize and address these desiderata and adapt their offerings to meet them.
Keywords: Controlled Medical Terminology; Vocabulary; Standards; Review